Childhood Injuries Due to Hay-Hole Falls: A 19-Year Experience at a Rural Pediatric Trauma Center. Issue 7 (July 2016) - Engbrecht, Brett W.; Kulaylat, Afif N.; Dias, Mark; Kendig, James W.; Cilley, Robert E.
Abstract : Objective: Children who live, work, and play on farms with barn design that includes hay-holes are at risk for a particular type of fall. This study retrospectively reviews all children admitted to a pediatric trauma center with injuries due to fall through a hay-hole over a 19-year period. This study is the first to specifically describe hay-hole fall injuries. Methods: A retrospective review from a 19-year period at a rural pediatric trauma center identified 66 patients who sustained injuries from a hay-hole fall. Charts were reviewed for patient demographics, injuries, interventions, and hospital course. Results: Sixty-six patients sustained injuries from hay-hole falls. Median patient age was 4 years, and median Injury Severity Score was 14. Forty-one percent of patients were admitted to the intensive care unit, and 26% of patients were intubated. Injuries included skull fracture (73%), facial fracture (27%), intracranial hemorrhage (53%), and noncraniofacial injuries (12%). Eighteen percent required a therapeutic intervention. There was 1 fatality (2%). Conclusions: Hay-hole fall appears to be a distinct injury mechanism, and patients present with different injury patterns than other types of falls. In this study, a high proportion of patients were young, and craniofacial injuries accounted for the majority of injuries. Only a small proportion of patients sustained noncraniofacial injuries. Injury prevention strategies should be targeted to this unique agrarian injury.